Analysis of Students’ Behavior in Solving Mathematical Literacy Problems at the Junior High School Level - Dwita Elfri Mayani; Heri Retnawati (International Journal of Applied Mathematics and Computing, 2026)
Background: Mathematical literacy is a key competency in 21st-century learning; however, Indonesian students’ achievement remains low. Previous research has largely focused on cognitive aspects, while behavioral dimensions such as self-regulation, the use of mathematical tools, and self-confidence have not received adequate attention, even though these aspects play a crucial role in successful problem-solving. Methods: This study employed a qualitative approach using grounded theory. Participants consisted of 18 eighth-grade students from three public junior high schools in Yogyakarta, selected through stratified random sampling. Data were collected through a mathematics literacy test, semi-structured interviews, and observations, and analyzed using constant comparison until data saturation was reached. Results: The analysis revealed a new behavioral category, termed “semi-superior,” situated between regular and superior behaviors. Self-regulation, the use of mathematical tools, and self-confidence interacted dynamically. Students with stronger self-regulation and higher self-confidence demonstrated more strategic and reflective approaches. A clear alignment was found between mathematical literacy proficiency and behavioral orientation. Implication: Mathematics instruction must integrate cognitive, metacognitive, psychomotor, and affective competencies. Future research should examine the socio-economic and technological factors that influence students’ mathematical literacy behaviors.